Green Awareness Effect on Consumers’ Purchasing Decision - I Made Surya Prayoga; Made Santana Putra Adiyadnya; Bagus Nyoman Kusuma Putra (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
Environmental conditions are influenced by the behavior of the community itself. In this transparent era public awareness as a consumer is very important. Green awareness is needed as a consideration for making purchasing decisions. Consumers must be careful in choosing products to consume. Production of green products requires efforts that make product prices higher than green products on the other hand high prices usually make it difficult for consumers to make purchasing decisions on that product. Companies must inform people of product specifications about the products they produce are green products. This research was conducted in well known tourist city in Indonesia, Denpasar, Bali by taking the subject of teenagers in Denpasar. using purposive sampling method with a total sample of 108 respondents. The results showed that environmental awareness has a positive but not significant effect on purchasing decisions. Green product awareness has a positive and significant effect on purchasing decisions. price awareness has a positive and significant influence on purchasing decisions and brand image awareness has a positive and significant effect on purchasing decisions.